2021
DOI: 10.3390/vaccines9010060
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Produced Antigen Displaying Virus-Like Particles Evokes Potent Antibody Responses against West Nile Virus in Mice

Abstract: In this study, we developed a hepatitis B core antigen (HBcAg)-based virus-like particle (VLP) that displays the West Nile virus (WNV) Envelope protein domain III (wDIII) as a vaccine candidate for WNV. The HBcAg-wDIII fusion protein was quickly produced in Nicotiana benthamiana plants and reached a high expression level of approximately 1.2 mg of fusion protein per gram of leaf fresh weight within six days post gene infiltration. Electron microscopy and gradient centrifugation analysis indicated that the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…These findings illustrate that a significantly lower dose of immunogen is required to elicit a potent immune response when the antigen is displayed on the surface of a particle, compared with the dose when it is used as an immunogen on its own. Interestingly, similar antibody titres to the soluble WNV-EDIII were observed in studies reported from a different laboratory where mice were immunised with 25 µg of either plant-produced soluble WNV-EDIII (He et al, 2014;Lai et al, 2018), or WNV-EDIII displayed on the surface of HBcAg (He et al, 2021). Their immunisation dose was five times more than what was used in our study, however, we observed similar or superior antibody binding titres with our lower dose of soluble WNV-EDIII and AP205:EDIII VLPs, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings illustrate that a significantly lower dose of immunogen is required to elicit a potent immune response when the antigen is displayed on the surface of a particle, compared with the dose when it is used as an immunogen on its own. Interestingly, similar antibody titres to the soluble WNV-EDIII were observed in studies reported from a different laboratory where mice were immunised with 25 µg of either plant-produced soluble WNV-EDIII (He et al, 2014;Lai et al, 2018), or WNV-EDIII displayed on the surface of HBcAg (He et al, 2021). Their immunisation dose was five times more than what was used in our study, however, we observed similar or superior antibody binding titres with our lower dose of soluble WNV-EDIII and AP205:EDIII VLPs, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…In a recent study by He et al HBcAg-WNV-EDIII VLPs were produced in N. benthamiana at a yield of 1.2 g/kg FLW (He et al, 2021 ). In this study, we report a yield of ~10 mg/kg FLW and from previous experiments, we have obtained a yield of purified AP205:EDIII VLPs of ~36 mg/kg FLW.…”
Section: Discussionmentioning
confidence: 99%
“…Only the results of sucrose gradient centrifugation suggested the assembly of prM-E VLPs [51]. They also fused wEDIII to HBcAg, and produced chimeric VLPs, which elicited strong B and T-cell responses against WNV in mice [204].…”
Section: West Nile Virus (Wnv)mentioning
confidence: 99%
“…This review describes work involving production in plants of domain III of the E protein of WNV (wEDIII), which was shown to be immunogenic [ 121 ] and probably even protective in mice [ 122 ], and hints at the production of the entire E protein as well as WNV VLPs produced in plants from expression of a prM-E construct, though this does not appear to have been published. There are, however, examples of wEDIII fused to HBcAg, which yields immunogenic core-like particles that stimulate an immune response against WNV in mice [ 123 ]. Using a similar strategy, domain III of the E protein of Zika virus (ZIKV, zEDIII) was displayed on the surface of HBcAg particles, and these were found to be highly immunogenic in mice [ 124 ].…”
Section: Flaviviridaementioning
confidence: 99%